Species differences in courtship acoustic signals among five Lake Malawi cichlid species (Pseudotropheus spp.) - Amorim, Maria Clara Pessoa (2012)
Male courtship acoustic signals from five Lake Malawi cichlid fish species of the Pseudotropheus zebra complex were recorded and compared. Sounds made by males of P. zebra, Pseudotropheus callainos and the undescribed species known as Pseudotropheus ‘zebra gold’ from Nkhata Bay, and Pseudotropheus emmiltos and Pseudotropheus faizilberi from Mphanga Rocks, differed significantly in the number of pulses and in pulse period. The largest differences in acoustic variables were found among the sympatric Mphanga Rocks species that, in contrast to the other three species, show relatively minor differences in male colour and pattern. These findings suggest that interspecific mate recognition is mediated by multimodal signals and that the mass of different sensory channels varies among sympatric species groups. This study also showed that sound peak frequency was significantly negatively correlated with male size and that sound production rate increased significantly with courtship rate.